Association between psychosocial functioning, health status and healthcare access of asylum seekers and refugee children: a population-based cross-sectional study in a German federal state - Diogo Costa; Louise Biddle; Kayvan Bozorgmehr (BMC, 2021)
Abstract Background The mental health condition and healthcare needs of asylum seeking and refugee (ASR) children may go unrecognized if barriers to healthcare access exist accompanied by exclusive focus on somatic illness. We analysed the relationship between psychosocial functioning, health status and healthcare access of ASR children. Methods During 2018, 560 ASR adults in 58 collective accommodations in Germany's 3rd largest federal state were randomly sampled and assessed. The parent-reported Strengths and Difficulties Questionnaire (SDQ) was used to assess child psychosocial functioning. SDQ dimensions (Emotional, Conduct, Peer, Hyperactivity, Prosocial, Total) were compared by demographics (sex, age, region of origin, time since arrival, subjective social status), health status (long-lasting illness, physical limitation, pain) and healthcare access (utilization: paediatrician, specialist, dentist, psychologist, hospital/emergency department, prescribed medicines; and unmet needs: for paediatrician/specialist, reduced spending to cover healthcare cost). Age and sex-adjusted odds ratios (AOR, 95%CI-Confidence Intervals) for scoring in borderline/abnormal ranges in SDQ dimensions were estimated through logistic regression depending on children' health status and healthcare access. Results We analysed parents' answers pertaining to 90 children aged 1-17 years old, 57% of which were girls and 58% with (Eastern or Western) Asian nationality. Scoring in the borderline/abnormal range of the SDQ Total Difficulties score was associated with feeling bodily pain (compared to no pain, AOR, 95%CI = 3.14, 1.21-8.10) and with an unmet need for a specialist during the previous year (4.57, 1.09-19.16). Borderline/abnormal SDQ Emotional scores were positively associated with a long-lasting illness (5.25, 1.57-17.55), physical limitation (4.28, 1.49-12.27) and bodily pain (3.00, 1.10-8.22), and negatively associated with visiting a paediatrician (0.23, 0.07-0.78), specialist (0.16, 0.04-0.69), and the emergency department (0.27, 0.08-0.96). Conclusion Poor psychosocial functioning among ASR children is associated with somatic problems, unmet medical needs, and lower healthcare utilisation. Somatic clinical encounters with ASR should include children' mental health symptomatology assessment, especially in those with worst physical health conditions.